A progressive muscle relaxation therapy to reduce stress levels in diabetic patients - Syam'ani, Syam'ani (GHMJ (Global Health Management Journal), 2022)
Type 2 diabetes is one of the major public health problems in both developing and developed countries in the Asia Pacific region. It cannot be denied that the psychological impact of diabetes mellitus has been felt by sufferers since the doctor's diagnosis. Patients begin to experience psychological disorders including stress on themselves related to treatment and medication that must be undertaken.  This photo essay pictures our effort in providing a progressive muscle relaxation to the diabetic patients as a therapy to reduce tension and anxiety. This technique focuses on the contraction and relaxation of the muscles of the body. the instructor demonstrate the steps of progressive muscle relaxation therapy to the participants.  The results of this study indicate that after being given progressive muscle relaxation therapy, there was a decrease in the number of diabetics who experienced stress, where before the intervention, there were 25 people with moderate stress (92.6%) and 2 people with severe stress (7,4%), while after the intervention decreased to 9 people (33.3%) had no stress, and 18 people (66.7%) had moderate stress.